2017
DOI: 10.5539/ijms.v9n2p134
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Brand Personality on Brand Loyalty: A Research on Automobile Brands in Turkey

Abstract: In this pilot study investigating the impacts of automobile brand personality perceptions of Turkish consumers on their attitudinal and behavioral intentions, the effects of the personality attributed to the brand by the consumers on their behavioral intentions regarding preferences, recommendations and willingness to pay higher prices for the brand are examined. The study consists of two main parts. Definitions of brand personality and brand loyalty are made in the literature review section where the conceptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
2
9
0
1
Order By: Relevance
“…Brand personality enables consumers to identify and connect with a brand, resulting in the sense of affection and dedication, so a consumer constantly purchases and uses a brand, therefore creating loyalty. The same results were achieved by Akin (2017)…”
Section: Research Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Brand personality enables consumers to identify and connect with a brand, resulting in the sense of affection and dedication, so a consumer constantly purchases and uses a brand, therefore creating loyalty. The same results were achieved by Akin (2017)…”
Section: Research Resultssupporting
confidence: 82%
“…Seimiene (2012) in her theoretical model of emotional connection between brand and consumer personalities concluded that the main traits of both brand and consumer personalities should be similar; in that way consumers will more likely choose a certain brand. Akin (2017) states that placing a product with a generic name directly leads to decreased market share since that product is now seen as common. It is also more difficult to establish good communication with prospective consumers since it is highly challenging to present such brand efficiently, and to make people remember a brand with a weak or no personality.…”
Section: Brand Personalitymentioning
confidence: 99%
See 2 more Smart Citations
“…According to Schiffman and Kanuk (2005), brand loyalty is customers' preference to make purchases on the same brand on specific products or certain service catalogs. Akin (2017) defines brand loyalty as repurchase points, preferences, recommendations, and attachments; its need for loyal customers for the sustainable competition is better understood. Loyalty is seen as one of the key elements to achieving permanent and long-term success in terms of business.…”
Section: Brand Loyaltymentioning
confidence: 99%